Will get fooled again: emotionally intelligent people are easily duped by high-stakes deceivers - Baker, Alysha (Legal and criminological psychology, 2013)
Purpose. There is major disagreement about the existence of individual differences in deception detection or naturally gifted detection ‘wizards’ (see O'Sullivan & Ekman, 2004 vs. Bond & Uysal, 2007). This study aimed to elucidate the role of a specific, and seemingly relevant individual difference - emotional intelligence (EI) and its subcomponents - in detecting high-stakes, emotional deception. Methods. Participants (N= 116) viewed a sample of 20 international videos of individuals emotionally pleading for the safe return of their missing family member, half of whom were responsible for the missing person's disappearance/murder. Participants judged whether the pleas were honest or deceptive, provided confidence ratings, reported the cues they utilized, and rated their emotional response to each plea. Results. EI was associated with overconfidence in assessing the sincerity of the pleas and greater self-reported sympathetic feelings to deceptive targets (enhanced gullibility). Although total EI was not associated with discrimination of truths and lies, the ability to perceive and express emotion (a component of EI), specifically, was negatively related to detecting deceptive targets (lower sensitivity [d′]). Combined, these patterns contributed negatively to the ability to spot emotional lies. Conclusions. These findings collectively suggest that features of EI, and subsequent decision-making processes, paradoxically may impair one's ability to detect deceit.